2003
DOI: 10.1097/01.phm.0000087453.94529.0d
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiagnostic Evidence of Phrenic Nerve Demyelination in Charcot-Marie-Tooth Disease 1A

Abstract: Our study confirms a dramatic phrenic nerve involvement in absence of clinical and laboratory evidence of diaphragmatic weakness; further studies and an adequate follow-up are necessary to discover whether the disease progress might encompass respiratory dysfunction at later stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Eichacker et al [26] evaluated a cohort with 10 patients committed by CMT1, with no respiratory complaints, but with muscular weakness present in most of the individuals studied. Sagliocco et al [27] observed reduced MEP in 100% of the individuals studied in the groups CMT1 and CMT2. It is worth pointing out that this study evaluated only individuals with CMT2 and from the same family.…”
Section: Discussionmentioning
confidence: 99%
“…Eichacker et al [26] evaluated a cohort with 10 patients committed by CMT1, with no respiratory complaints, but with muscular weakness present in most of the individuals studied. Sagliocco et al [27] observed reduced MEP in 100% of the individuals studied in the groups CMT1 and CMT2. It is worth pointing out that this study evaluated only individuals with CMT2 and from the same family.…”
Section: Discussionmentioning
confidence: 99%
“…One large study included 200 patients with CMT1A, of whom 40 reported respiratory symptoms and 15 showed possible respiratory muscle weakness, as roughly estimated by FVC <80% of predicted and maximal inspiratory pressure <40 cmH 2 O . Another study including 11 patients electrophysiologically demonstrated phrenic nerve involvement, even in the absence of respiratory complaints or abnormal FVC and mouth occlusion pressures . A third study documented altered phrenic nerve morphology on ultrasound and prolonged latencies on phrenic NCS in 16 patients with CMT1A; reduction of PImax and PEmax was present in 5 and 12 patients, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with CMT1A rarely have clinical respiratory symptoms, despite severe nerve demyelination and some diaphragmatic dysfunction. Sagliocco et al investigated the correlation between electrophysiologic findings and clinical respiratory signs, or spirometric abnormalities in patients with CMT1A, and showed that phrenic nerve conduction velocities were significantly slower (p < 0.0001; median conduction time, 18.6 ms; 95th percentile, 31.97 ms) than that recorded in the control group of healthy subjects (median, 6.05 ms; 95th percentile, 8.82 ms) but none of them had clinical or laboratory evidence of diaphragmatic weakness ( Sagliocco et al, 2003 ) . These findings may be compatible with the other observations that there is no correlation in CMT between strength and nerve conduction velocity in the limbs, unless severe weakness is present ( Dyck et al, 1993 ) .…”
Section: Hereditary Peripheral Neuropathiesmentioning
confidence: 92%